The dangers of blind trust: Examining the interplay among social media news use, misinformation identification, and news trust on conspiracy beliefs. (November 2021) - Xiao, Xizhu; Borah, Porismita; Su, Yan
Since the beginning of the COVID-19 pandemic, misinformation has been circulating on social media and multiple conspiracy theories have since become quite popular. We conducted a U.S. national survey for three main purposes. First, we aim to examine the association between social media news consumption and conspiracy beliefs specific to COVID-19 and general conspiracy beliefs. Second, we investigate the influence of an important moderator, social media news trust, that has been overlooked in prior studies. Third, we further propose a moderated moderation model by including misinformation identification. Our findings show that social media news use was associated with higher conspiracy beliefs, and trust in social media news was found to be a significant moderator of the relationship between social media news use and conspiracy beliefs. Moreover, our findings show that misinformation identification moderated the relationship between social media news use and trust. Implications are discussed.